BIOCHEMICAL PARAMETERS OF YOUNG RABBITS MEAT UNDER DIFFERENT DOSES OF SULFUR IN THE DIET - Шулько, О. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The different levels of Sulfur (0;2; 0;3; 0;4 and 0;5 %) in the form of sodium sulfate and the background level of Selenium (0;2 mg/kg dry matter intake) on biochemical indicators of young rabbits meat. To improve the technology growing rabbits need to adjust and improve nutrition standards. Important role in balancing rations for all the necessary nutrients play a macro and micronutrients. In particular; to date; in the absence of rules oriented introduction of Sulfur and Selenium in the diets of rabbits and their optimum ratio is relevant studies on their impact on the performance of young rabbits. It is known that Sulfur is part of the organic compounds – proteins; amino acids; vitamins; involved in the biosynthesis of hair keratins. Along with Sulfur indispensable power factor also believe Selenium because it works closely with the micro-and macronutrients; vitamins and enzymes as in the environment (water; soil; plants) and in animals and humans. At the end of the experiment conducted control slaughter of rabbits (3 heads of each group) to determine the morphological; chemical and biophysical parameters slaughter products. To do this; samples were taken meat; liver; kidneys; heart; lungs; spleen; bones; fur. In the main period of the experiment the animals in the control group received complete feed; balanced according to detailed rules. The difference in feeding rabbits experimental groups compared with control; was that the composition of feed for animals 2; 3; 4 and 5th research groups additionally was administered sodium sulfate as the source of Sulfur in doses of 2; 3; 4 and 5 g/kg; respectively; on dry matter intake; and to ensure the optimal level of Selenium – 0;2 mg/kg of dry matter intake - additionally was administered sodium selenite. However take into account natural Sulfur content (1 g/kg) and Selenium (0;09 mg/kg of dry matter feed) to feed. On the impact of the studied doses of Sulfur in the background add to the optimum level of inorganic Selenium judged by the analysis of the pectoral muscle Thus; elevated levels of Sulfur in the diet to 2-5 g/kg dry matter of feed positively influenced the content of the rabbit dry and organic matter; protein and nitrogen free extract. In this case; of Sulfur intake rabbits at 3;4 g/kg the best results are marked by the introduction. For a comprehensive assessment of the optimal dose is Sulfur – 0;4% for the Selenium level of 0;2 mg/kg dry matter intake and feeding complete feed with optimum Sulfur and Selenium leads to improvement of biochemical parameters of rabbits meat.